Identification and verification of hub biomarkers and immune-related pathways participating in the trabecular meshwork after using corticosteroid - Liwen Wang; Di Wu; Ziwei Ma; Di Song; Yuanqiang Sun; Xuefeng Pan; Junhui Zhang (PLoS ONE, 2025)
Background Clinically, ocular application of corticosteroids is common.But it always result in higher Intraocular pressure (IOP).The potential molecular events are not clearly explained.It was reported that immune cells may cause higher IOP.This study aimed to identify the central gene and immune-related pathways in ocular tissue treated with corticosteroids. Methods The GSE124114 and GSE37474 was obtained from Gene Expression Omnibus database. Hub gene were acquired by differential expression analysis (DEGs).Weighted gene co-expression network analysis (WGCNA) identified hub gene modules associated with elevated intraocular pressure (IOP).CIBERSORT was utilized to evaluate the presence of immune cells in ocular tissue.R (version 3.6.1) was used to carry out enrichment analysis for DEGs.The STRING database constructed the protein-protein interaction network for differentially expressed genes (DEGs).The expression of hub genes was validated using the combined datasets GSE6298 and GSE65240. ROC analysis was conducted for clinical diagnosis in patients with elevated IOP. Results 30 DEGs were recognized. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses revealed that these DEGs were mainly associated with the positive regulation of cytokine production and pathways related to phenylalanine metabolism.Two hub modules were enriched in the rheumatoid arthritis and AGE-RAGE signaling pathways associated with diabetic complications. Analysis of the protein-protein interaction (PPI) network identified TSC22D3 and FKBP5 as related hub genes. Analysis of immune infiltration indicated a significant association between TSC22D3 and Macrophages M0 (R = 0.75, p = 0.018).The result of ROC for FKBP5 was 0.913.Consolidated GSE6298, GSE65240 database verified that FKBP5 gene was associated with IOP.In the results of qPCR, relative mRNA level of FKBP5 were incread. Conclusions Two key genes (TSC22D3, FKBP5) are involved in the molecular mechanisms in corticosteroids-induce higher IOP. TSC22D3 was probably associated with the immune response in ocular tissue. FKBP5 may be a potential novel diagnostic gene for higher IOP.